Clinical and bacteriological diagnosis agreement in vaginal and cervical infections - Cubas Vásquez, Víctor (2015)
OBJETIVE: To determine the degree of concordance between the clinical diagnosis and bacteriological diagnosis in vaginal and cervical infections. METHODS: Using a cross-sectional study, 1,252 women were included in 4 family planning clinics in Lima, Peru. Clinical diagnoses 4 gynecologists with laboratory diagnosis of vaginal and cervical fluid was compared. Prevalence of vaginal and cervical infections, clinical validity and consistency with respect to the bacteriological diagnosis was calculated using kappa index. RESULTS: Prevalence of infection by laboratory diagnosis: Bacterial vaginosis 250 (20%), cervical infection with Chlamydia trachomatis or Neisseria gonorrhoeae 143 (11.4%), candidiasis 60 (4.8%) and trichomoniasis 40 (3.2%). 250 clinical diagnosis of bacterial vaginosis was confirmed in 91 (36.4%) (k 0.2), 143 cervicitis clinical diagnoses was confirmed in 20 (13.9%) (k: 0.05), 60 candidiasis was confirmed in 26 (43.3%) (k 0.1) and 40 clinical diagnoses trichomoniasis was confirmed in 8 (20%) (k: O, 05). CONCLUSIONS: No correlation between clinical and bacteriological diagnosis of vaginal and cervical infections, resulting in improper handling was found. It is recommended that simple bacteriological examinations, pH and Amines test and take into account associated epidemiologic factors to improve diagnosis.